A REVIEW OF EXPERIMENTAL METHODS IN BUILDING WALL THERMAL INSULATION: PHYSICAL, DIGITAL, AND HYBRID APPROACHES - Kasman, Tamiya Miftau Saada; Wonorahardjo, Surjamanto; Larasati, Dewi; Widiastuti, Indah (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2025)
The implementation of thermal insulation within the walls of building constitutes a pivotal strategy aimed at mitigating cooling loads and augmenting energy efficiency, particularly in tropical climate conditions. In the preceding decade, scholars have progressively utilized both empirical and computational methodologies to evaluate the efficacy of insulation under diverse environmental and material parameters. Aims: This study undertakes a comprehensive review of methodological frameworks in the domain of thermal insulation research for building walls conducted between 2020 and 2024, with an emphasis on hybrid experimental design that integrate physical measurements with digital simulations to yield more accurate, dependable, and contextually pertinent data. Methodology and results: A systematic literature review (SLR) encompassing 52 scholarly articles was performed, categorizing the studies into four distinct classifications: field studies, laboratory-based investigations, digital methodologies (e.g., EnergyPlus, TRISCO, ABAQUS), and hybrid methodologies. Among these, digital experimentation emerged as the most predominant methodology, with EnergyPlus identified as the most frequently utilized instrument. Research employing hybrid methodologies demonstrated enhanced analytical rigor through cross-validation, versatile scenario exploration, and comprehensive thermal performance assessment. Conclusion, significance, and impact study: Combining empirical data with digital experimentation significantly improves the precision and contextual relevance of thermal insulation evaluation. Hybrid methodologies facilitate the simulation of prolonged or extreme conditions that are often impractical to physically assess. Calibrated digital instruments such as EnergyPlus, TRISCO, ABAQUS, Delphin, and COMSOL are particularly effective. Especially for tropical climates, hybrid methodologies offer a robust framework for improving the design, applicability, and performance of building insulation systems.